Evaluation and optimization of ethanol production from carob pod extract by Zymomonas mobilis using response surface methodology - Vaheed, Hossein; Shojaosadati, Seyed Abbas; Galip, Hasan (Springer Heidelberg, 2011)
In this research, ethanol production from carob pod extract (extract) using Zymomonas mobilis with medium optimized by Plackett-Burman (P-B) and response surface methodologies (RSM) was studied. Z. mobilis was recognized as useful for ethanol production from carob pod extract. The effects of initial concentrations of sugar, peptone, and yeast extract as well as agitation rate (rpm), pH, and culture time in nonhydrolyzed carob pod extract were investigated. Significantly affecting variables (P = 0.05) in the model obtained from RSM studies were: weights of bacterial inoculum, initial sugar, peptone, and yeast extract. Acid hydrolysis was useful to complete conversion of sugars to glucose and fructose. Nonhydrolyzed extract showed higher ethanol yield and residual sugar compared with hydrolyzed extract. Ethanol produced (g g(-1) initial sugar, as the response) was not significantly different (P = 0.05) when Z. mobilis performance was compared in hydrolyzed and nonhydrolyzed extract. The maximum ethanol of 0.34 +/- A 0.02 g g(-1) initial sugar was obtained at 30A degrees C, initial pH 5.2, and 80 rpm, using concentrations (g per 50 mL culture media) of: inoculum bacterial dry weight, 0.017; initial sugar, 5.78; peptone, 0.43; yeast extract, 0.43; and culture time of 36 h.
3rd International Conference on Environmental, Industrial, and Applied Microbiology (BioMicroWorld 2009) -- DEC 02-04, 2009 -- Lisbon, PORTUGAL
Keywords: Carob pods; Ethanol; Fermentation; Response surface methodology; Zymomonas mobilis